Heavy metal contamination in surface sediments: A comprehensive, large-scale evaluation for the Bohai Sea, China. (May 2020) - Wang, Xuejing; Fu, Renlong; Li, Hailong; Zhang, Yan; Lu, Meiqing; Xiao, Kai; Zhang, Xiaolang; Zheng, Chunmiao; Xiong, Ying
Abstract: Heavy metal contamination in the Bohai Sea (China) has been the focus of many studies, but most of them only focused on local pollution levels and thus lacked high spatial resolution for the whole sea. In this study, heavy metals (i.e., As, Cr, Cu, Cd, Pb, Zn, and Fe) in surface sediments were analyzed to assess the spatio-temporal pollution conditions of the Bohai Sea, an important coastal environment consisting of Bohai Bay, Laizhou Bay, and Liaodong Bay. The results indicated that the heavy metal concentration in the sediments was in the range of 6.43–32.18 mg/kg for As, 14.90–58.07 mg/kg for Cr, 3.90–27.19 mg/kg for Cu, 0.04–0.27 mg/kg for Cd, 11.09–30.95 mg/kg for Pb, 18.76–65.58 mg/kg for Zn, and 0.78%–2.55% for Fe. The distribution of heavy metals revealed that the concentrations were relatively low in Laizhou Bay, very high in the northwest coastal region of the Bohai Sea, and decreased from near-shore to off-shore areas. Moreover, both the enrichment factor and geo-accumulation index demonstrated that there was no contamination to be found for Cr, Cu, Zn in the region and a slight to moderate pollution of As, Cd, and Pb. Cd and As presented considerable potential ecological risk as a result of their high toxicity. The potential ecological risk index (RI) suggested that a third of the areas (northwest coastal area of the Bohai Sea) has moderate ecological risk. The risk area was generally decreased as offshore distance increased, which suggested that the contamination and risk of heavy metals are influenced by anthropogenic activities. Graphical abstract: Image 1 Highlights: Heavy metal pollution with high spatial resolution was evaluated in the Bohai Sea. The concentrations of all of the metals except As decreased in the last decade. Coastal areas and estuaries experienced more serious contamination than other areas. Cd and As presented a slight to moderate contamination and potential ecological risk. Abstract : Heavy metals, especially Cd and As, presented more serious contamination and potential ecological risk in the northwest coastal areas and estuaries of the Bohai Sea.